An active factor from tomato root exudates plays an important role in efficient establishment of mycorrhizal symbiosis. - Shubin Sun (Public Library of Science (PLoS), 2012)
Root exudates play an important role in the early signal exchange between host plants and arbuscular mycorrhizal fungi. M161, a pre-mycorrhizal infection (pmi) mutant of the tomoto (Solanum lycopersicum) cultivar Micro-Tom, fails to establish normal arbuscular mycorrhizal symbioses, and produces exudates that are unable to stimulate hyphal growth and branching of Glomus intraradices. Here, we report the identification of a purified active factor (AF) that is present in the root exudates of wild-type tomato, but absent in those of M161. A complementation assay using the dual root organ culture system showed that the AF could induce fungal growth and branching at the pre-infection stage and, subsequently, the formation of viable new spores in the M161 background. Since the AF-mediated stimulation of hyphal growth and branching requires the presence of the M161 root, our data suggest that the AF is essential but not sufficient for hyphal growth and branching. We propose that the AF, which remains to be chemically determined, represents a plant signal molecule that plays an important role in the efficient establishment of mycorrhizal symbioses.